2020
DOI: 10.1016/j.cdtm.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Jian Pi Qu Shi Formula on intestinal bacterial flora in patients with idiopathic membranous nephropathy: A prospective randomized controlled trial

Abstract: BackgroundThe incidence of idiopathic membranous nephropathy (IMN) has recently increased remarkably. Immune dysfunction caused by disordered intestinal flora might be an important factor affecting IMN. The Jian Pi Qu Shi Formula (JPQSF) shows promise in treating IMN. Here, we sequenced 16S rRNA genes to compare intestinal flora between patients with IMN and healthy persons. We also conducted a randomized controlled clinical trial to further compare the intestinal flora of patients with IMN treated with tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Bacteroides can produce short-chain fatty acids in the colon, and significantly enhance the growth of colonic lamina propria Treg cells after colonization. Such enhancement further exerts immunomodulatory effects [ 22 ]. Faecalibacterium is abundant in the fecal microbiome of healthy humans.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroides can produce short-chain fatty acids in the colon, and significantly enhance the growth of colonic lamina propria Treg cells after colonization. Such enhancement further exerts immunomodulatory effects [ 22 ]. Faecalibacterium is abundant in the fecal microbiome of healthy humans.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the total effect of α -ketoacid is repairing intestinal barrier in Adenine-induced CKD rats. Coprococcus_3 is one of the main genera that differed between the patients with idiopathic membranous nephropathy and healthy groups ( Lang et al, 2020 ). It is also reported that the genera of Coprococcus three in the ileum were correlated positively with lipid metabolic dysfunction and pro-inflammatory response in low-birth-weight pigs ( Huang et al, 2020 ), which is in accord with our finding that abundance of Coprococcus_3 was positively correlated with serum level of TMAO and IS.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 78 potentially eligible articles were obtained from the literature search, and five studies ( Dong et al, 2020 ; Lang et al, 2020 ; Yu et al, 2020 ; Zhang et al, 2020 ; Li et al, 2022 ) were eventually included ( Figure 1 ). All studies were of the case-control type, with four studies using healthy individuals as controls (HCs) and one study using patients with diabetic kidney disease (DKD) as the control group.…”
Section: Resultsmentioning
confidence: 99%
“…The enrichment of Actinobacteria was observed in patients with IMN compared with HCs (Li et al, 2022) and Frontiers in Physiology frontiersin.org in one group of DKD patients (Yu et al, 2020). The variations in the abundance of Bacteroidetes were inconsistent; it was increased in one study (Lang et al, 2020), but decreased in two studies (Yu et al, 2020;Li et al, 2022) (Supplementary Table S6). In all studies (Dong et al, 2020;Lang et al, 2020;Yu et al, 2020;Zhang et al, 2020;Li et al, 2022), the alteration of gut microbiota was evaluated at the genus level.…”
Section: Differences In the Abundance Of Bacterial Taxamentioning
confidence: 98%
See 1 more Smart Citation